Feasibility of an Isometric Maximal Voluntary Contraction Test in Hematological Cancer Patients during Thrombocytopenia - Zimmer, Philipp (J Sports Med (Hindawi Publ Corp), 2013)
Introduction. Resistance training is rarely offered to hemato-oncological patients in the daily clinical routine due to its potential harmful impact on the cardiovascular system and the long periods of thrombocytopenia experienced by these patients. Therefore, it is important to determine a valid assessment to define and control resistance training. In this study, the feasibility of a maximal voluntary contraction (MVC) test was investigated in hemato-oncological patients. This inexpensive assessment may be a practicable alternative to the one repetition maximum test which is currently described as the gold standard. Methods. 29 hemato-oncological patients with platelet counts between 30000/μL and 70000/μL were recruited for this pilot study. Complications like petechial bleedings, muscle convulsion, and pain were assessed using the Brief Pain Inventory before and 48 hours after the MVC test, which was performed unidirectionally for the quadriceps muscle. Results. We did not detect any statistically significant test-related exacerbations or pain development. Discussion. MVC testing seems to be a feasible method to control a resistance training program in hemato-oncological patients. Further studies need to extend their methods and, for example, compare the MVC test with the one repetition maximum test.